The Human Resource Management in Islamic Education - Zuharisdin Yusuf; Roudhotun Ni'mah; Elviyati; Dewi Hajarul Husna; Husni Ginting Pamungkas; Galuh Ayudya Hadi; Nurul Hidayati Murtafiah (The Future of Education Journal, 2024)
Human Resource Management (HR) in Islamic education is an important aspect in realizing optimal education quality. This article discusses the concept and strategy of HR management in the context of Islamic education, focusing on the important role of educators, education managers, and other stakeholders in creating a conducive environment for student development. Islamic education emphasizes moral and spiritual values ​​in the learning process, so HR management must involve aspects of faith, ethics, and professional competence. The managerial approach in HR management in Islamic education includes recruitment, training, evaluation, and career development of educators that are not only based on academic ability, but also on personality and faith qualities. In this case, effective HR management can improve educator performance and improve the overall quality of education. Therefore, HR management in Islamic education is not only aimed at producing quality educators, but also at forming people with noble morals, in accordance with Islamic teachings. This article is expected to provide insight for education managers in designing and implementing a better HR management system in Islamic educational institutions.